Selective chemical control of yellow bristle grass (Setaria pumila) in pasture - James, T.K.; Rahman, A. (New Zealand Plant Protection, 2009)
Yellow bristle grass (Setaria pumila) is a summergrowing annual grass currently expanding in distribution throughout pastures in Waikato Readily grazed in its early vegetative growth stage it is avoided by animals when the seed heads appear as barbed bristles lead to animal health problems particularly around the mouth Three field trials were conducted with several herbicides for control of yellow bristle grass Since yellow bristle grass germinates over an extended period from November to February the best control that could be achieved from a single herbicide application was 70 by 22DPA alone or in combination with either TCA or carbetamide applied in December MSMA was more effective on larger plants Ethofumesate treatment resulted in poor control of yellow bristle grass and severe damage to white clover (Trifolium repens) All herbicides evaluated resulted in variable levels of damage to perennial ryegrass (Lolium perenne)